Sistema de rastreamento de sementes sementes GeoRaster - Fumagalli Junior, Edson Machado (2013)
The increasing advance of technological artifacts and new manners of monitoring have become possible to know the origins of the seeds. Using applied technologies and Internet it is possible to store and access data in geographic databases which allow viewing and keeping up with all the accomplished work in the prior years in conjunction with the precision agriculture data and handlings associated to the seeds origin.Web programming tools and databases permit the integration with the data of precise agriculture, resulting in an origin history and production of seeds previously recorded.The application of geotechnologies and the spatial data of sowing places makes possible to verify the existence of agricultural activities in determined area and, at the same time, to use the information stored in the database generated by precise agriculture software of various suppliers. The results of this research can help the initiatives to elaborate projects and full monitoring of agricultural production and seed certification.